Access to digital media and devices and their Impact on the use of technology in the teaching of African literature in Gauteng classrooms - Mahao, Mahao; Gennrich, Toni (African Perspectives of Research in Teaching & Learning (APORTAL), 2022)
This study investigates the factors that enable or constrain teachers’ access to digital media and devices and how these impact the use of technology in African literature lessons in selected Gauteng schools. The South African Department of Basic Education’s (DBE) plan to incorporate technology in education coupled with their desire to include more African texts in the literature syllabus may be in tune with fast changing digital landscapes and a drive towards the decolonisation of teaching and learning, but the reality of some school contexts and how this impacts access to digital technology makes these ideas difficult to implement. The study is drawn from a larger one that examined the technology ideals, primarily how they related to the use of digital media and devices in the researching and teaching of African literary texts, of the Department of Basic Education and the disconnect between these and the existing realities in some school contexts. The study focuses on two teachers’ use of technology in two very different contexts in the same province, Gauteng. The study used qualitative methodology, relying on interviews and contextual scans. The findings revealed a disharmony between the (2004) proposals by the DBE to transform learning and teaching using ICTs and, 20 years later, how the reality of teachers’ contexts makes these proposals seem difficult to attain. Some teachers are resistant and appear frustrated by their access to both technology and information on the internet. In certain contexts, where the proposals are implementable, other societal ills counter the DBE’s good intentions. Recommendations of this study are that there should be support and training of teachers to ensure that they develop the confidence to use technology generally and to use collaborative digital tools to bring an African lens to African literary texts. There needs to be support from the DBE to provide access and security, and there should be transparency in these processes.
Journal article published in African Perspectives of Research in Teaching & Learning Journal (APORTAL) Vol 6 (2) (2022)
Keywords: Access; African literature; Decolonisation; Mindsets; Technology in education; Digital media; Basic education; African literature; Computer-assisted instruction